2008
DOI: 10.1149/1.2965495
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Atomic-Layer-Deposited Al[sub 2]O[sub 3] High-k Dielectric Films Grown on Ge Substrates

Abstract: This paper describes the structural and electrical properties of Al 2 O 3 thin films grown through atomic layer deposition onto Ge substrates over a wide deposition temperature range ͑50-300°C͒. From grazing-incidence X-ray reflectivity and X-ray photoelectron spectroscopy, we found that increasing the deposition temperature improved the Al 2 O 3 film density and its dielectric stoichiometry; nevertheless, dielectric intermixing between main Al 2 O 3 and interfacial GeO 2 appeared at temperatures above 200°C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…3͑a͒ inset͔ in case of T dep = 250°C most likely due to an increased outdiffusion of GeO x species from the interface. A similar observation has been reported in the case of ALD of Al 2 O 3 at T dep Ͼ 200°C, 11 which leads to defect generation and thus to a degradation of the electrical interface performance. 12 In general, the small ac voltage ͑30 mV͒ applied to the gate causes changes in the occupancy of interface trap levels around a few kT / q of the Fermi-level, which leads to losses at all frequencies, as shown in Fig.…”
Section: Process Temperature Dependent High Frequency Capacitance-volsupporting
confidence: 80%
“…3͑a͒ inset͔ in case of T dep = 250°C most likely due to an increased outdiffusion of GeO x species from the interface. A similar observation has been reported in the case of ALD of Al 2 O 3 at T dep Ͼ 200°C, 11 which leads to defect generation and thus to a degradation of the electrical interface performance. 12 In general, the small ac voltage ͑30 mV͒ applied to the gate causes changes in the occupancy of interface trap levels around a few kT / q of the Fermi-level, which leads to losses at all frequencies, as shown in Fig.…”
Section: Process Temperature Dependent High Frequency Capacitance-volsupporting
confidence: 80%
“…Therefore, the density of the ALD Al 2 O 3 films is expected to decrease slightly when the growth temperature decreases. In other reports, the density of the film grown via ALD largely decreases with decreasing growth temperature due to severely increasing content of residual impurities in the film 14 , 17 . However, only a slight reduction in the refractive index of the film with decreasing temperature was observed, indicating a slight decrease in the density, which is confirmed by the XRR results plotted in the inset of Fig.…”
Section: Resultsmentioning
confidence: 84%
“…The lower D incorporation observed for Ge samples may be related to the theoretically predicted resistance of Ge dangling bonds to H passivation 6 and/or instability of Ge-H bonds. 11 Nevertheless, previous reports showed that the use of FGA in the 300-400 C temperature range presented a reduction in the D it figures in structures like HfO 2 /GeO x N y /Ge, 3 Al 2 O 3 /Ge, 7 and GeO 2 /Ge. 8 These results, in conjunction with our observation that most of the D is incorporated near the HfO 2 /Ge interface region, point to a H-related passivation effect.…”
mentioning
confidence: 96%
“…On the other hand, a significant reduction in D it figures is observed for gate stacks following FGA. 3,7,8 This apparent contradiction indicates the need for further understanding of the hydrogen (H) role in the electrical and physico-chemical properties of dielectric films on Ge. In view of this scenario, we investigated the thermally-induced interaction of H with HfO 2 films deposited on Ge and Si substrates.…”
mentioning
confidence: 99%